2018
DOI: 10.3390/ijms19041072
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bicarbonate Secretion in Marine Fish Intestine by the Calcium-Sensing Receptor

Abstract: In marine fish, high epithelial intestinal HCO3− secretion generates luminal carbonate precipitates of divalent cations that play a key role in water and ion homeostasis. The present study was designed to expose the putative role for calcium and the calcium-sensing receptor (CaSR) in the regulation of HCO3− secretion in the intestine of the sea bream (Sparus aurata L.). Effects on the expression of the CaSR in the intestine were evaluated by qPCR and an increase was observed in the anterior intestine in fed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This disparity in response amplitude between the toadfish [15,52] and the seabream (this study) could be related to calcium concentrations in intestinal fluids, which are higher in sea bream than in toadfish (> 2-fold). It is likely that luminal calcium functions as a limiting factor for precipitation in the intestine of the toadfish [17] and we have shown the calcium dependency of intestinal bicarbonate secretion in the sea bream [68]. In addition, it was previously reported that the sea bream responds to hypercapnia with a plasma pH drop, which is buffered within the first 5 days of exposure by increasing plasma bicarbonate levels [29].…”
Section: Discussionmentioning
confidence: 78%
“…This disparity in response amplitude between the toadfish [15,52] and the seabream (this study) could be related to calcium concentrations in intestinal fluids, which are higher in sea bream than in toadfish (> 2-fold). It is likely that luminal calcium functions as a limiting factor for precipitation in the intestine of the toadfish [17] and we have shown the calcium dependency of intestinal bicarbonate secretion in the sea bream [68]. In addition, it was previously reported that the sea bream responds to hypercapnia with a plasma pH drop, which is buffered within the first 5 days of exposure by increasing plasma bicarbonate levels [29].…”
Section: Discussionmentioning
confidence: 78%
“…Further, the rate of precipitation in the first 24 h after SW transfer was influenced by the dEB of the freshwater feeds. In the L-dEB fed fish, it is likely that intestinal HCO 3 − secretion and calcium sensing receptor (CsR) were influenced by dietary CaCl 2 as in gilthead seabream in vitro (Gregório et al, 2019;Gregório and Fuentes, 2018). Whereas, in the H-dEB fed fish, carbonate ions directly derived from dietary Na 2 CO 3 could be have increased the formation of ICP in this group.…”
Section: Tablementioning
confidence: 94%
“… Forward (Fw) and reverse (Rv) primers; annealing temperature (Ta); base pairs (bp). a [ 24 ]; b [ 42 ]. …”
Section: Figurementioning
confidence: 99%
“…There are vital pieces of evidence concerning the regulation of both STC and PTHrP through a CaSR, a unique novelty receptor firstly described in bovine parathyroid [ 23 ]. Over the last two decades, the CaSR has received particular attention, especially in marine fish, due to its importance in maintaining the water and ionic balance [ 24 ]. As it belongs to the G protein-coupled receptor (GPCR) superfamily, it induces the activation of different types of G protein [ 25 ] when stimulated by calcium or other agonists, such as calcimimetics, or inhibited by calcilytics [ 26 ].…”
Section: Introductionmentioning
confidence: 99%